(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
The scope of takzir sentence in Islamic law is wide-ranging and not limited to fine, prison and whipping as provided by the Syariah Court Act (Criminal Jurisdiction) Act 1965 (Amended 1984) [Act 355]. This Act has been amended in 1984. Unfortunately, it still does not fulfil the genuine spirit of uqubah takzir in Islam. Criminal jurisdiction of the Syariah Court is still limited with fine not exceeding RM5000 orimprisonment for a term maximum three years, or whipping not exceeding six strokes or with any combination thereof. Under Islamic law, amendments and improvements of takzir sentence is necessary to ensure that it is responsive to changes and relevant with the current situation. This paper therefore, will discuss the wide scope of takzir sentences as has been shown in the early period of Islam, its implementation in the present syariah court, the obstacles that prevent its transformation and its solutions. Perhaps a real understanding on takzir sentence in Islamic law will serve as a paradigm shift in the efforts to improve the existing takzir sentence in the syariah courts towards a better position and relevant with the current situation. Keywords: takzir sentence, Islamic law, criminal jurisdiction, syariah courts